Towards efficient hydropower harvesting: Design modification and performance optimization of a spherical lift-based in-pipe turbine - Mohammad J. Rostamani; Peyman Sobhani; Nima Hasanzadeh; Amir F. Najafi (Results in Engineering)
The growing global demand for sustainable energy has intensified efforts to identify alternative power generation methods that can be integrated into existing infrastructure. One promising approach involves harvesting energy from high-pressure flows in water distribution networks using small-scale, lift-based turbines. However, conventional lift-based turbines typically exhibit low power output and efficiency when deployed within pipelines. To address these limitations, this study introduces a novel design that varies the chord length of the turbine blade's cross-section. The design maintains a consistent initial angle of attack along the blades, reducing flow blockage near the upper and lower hub and enhancing torque generation by increasing the chord length at the turbine mid-sections. Numerical simulations and experimental tests demonstrate that this configuration improves the power coefficient by 50 % compared to traditional designs. Following the validation of the approach, a comprehensive numerical dataset covering a wide range of geometric and operational parameters was developed to imply a multi-objective optimization process. This resulted in an optimized turbine design with a power coefficient of 0.53 and an efficiency of 22 %.